Strategies for Recruiting and Developing Islamic Religious Education Teachers in the Digital Era - Dian Hikmayana (CV. Agrapana Media, 2025)
This study examines the recruitment strategies and professional development processes of Islamic Education (PAI) teachers in the digital era. The main issue identified is the limited use of technology in teacher selection and training, which results in learning quality that has not fully met 21st-century demands. The purpose of this study is to analyze digital-based recruitment strategies for PAI teachers and to explore effective forms of professional development in responding to educational transformation. Using a library research method, this study reviews literature on digital recruitment, teacher professionalism, and technology integration in Islamic education. The findings show that digital recruitment—through online platforms, technology-based assessments, and virtual interviews—enhances the efficiency and objectivity of the selection process and ensures that candidates possess sufficient pedagogical competence and digital literacy. Furthermore, continuous professional development involving technology training, learning communities, self-evaluation, and spiritual reinforcement contributes significantly to improving the quality of PAI teachers. The study implies that Islamic educational institutions must integrate technology throughout their human resource management processes to prepare adaptive, professional, and values-driven PAI teachers capable of meeting the challenges of the digital era.